Understanding host-microbiome interactions -- an omics approach : omics of host-microbiome association - Singh, Ravindra Pal; Kothari, Ramesh; Koringa, Prakash G.; Singh, Satya Prakash (Springer, 2017)
This book offers up-to-date information on different microbiomes, their community composition and interactive functions with the host, bringing together information from diverse research reports to provide an overview of the rapid developments in meta-omics technologies. It is a valuable resource for scientists, researchers, postgraduate and graduate students interested in understanding the impact and importance of next generation sequencing technologies on different hosts and their microbiomes.
Keywords: Host-parasite relationships.; elektronické knihy; electronic books